Large scale implementation of a medicines reconciliation care bundle in NHS GGC GP practices. Issue 1 (7th November 2016) - Bruce, Rachel
Abstract : Medicines reconciliation (MR) is an essential process for patient safety, promoting safer use of medicines with effective communication at the interface, particularly when patients are admitted and discharged from hospital. Much of the work on MR has been focussed in secondary care, however, the principles are equally important in primary care. The aim of the work was to test the Scottish Patient Safety in Primary Care (SPSP-PC) MR care bundle and consider scale up and spread across all NHS Greater Glasgow and Clyde (NHS GGC) GP practices. Care bundles are a quality improvement tool which can drive improvement by standardising processes to deliver optimum care. Pilot work and testing began with 5 GP practices in 2011 and was spread to over 200 practices by 2015/16. A care bundle compliance process measure was measured monthly, with practices sampling 10 patients per month. Practices could view their run charts in real time and identify which measures resulted in "non-compliance" and PDSA cycles were promoted to test and implement improvements. Data was collated at NHS GGC level with an aim of 95% compliance with the care bundle by March 2016. MR care bundle compliance started at 40% (5 practices reporting) in 2011 with final data in March 2016 demonstrating 92% compliance (192 practices reporting). A sustained "reliability" of 92-93% across >200 practices has been observed since January 2015. In conclusion, the bundle was implemented by 97% of NHS GGC GP practices and resulted in process improvements.